2014
DOI: 10.1002/ace.20105
|View full text |Cite
|
Sign up to set email alerts
|

Youths Transitioning as Adult Learners

Abstract: This chapter considers how transitions to adulthood have been historically represented and presents alternative ways of thinking about transitions to adulthood through the context of adult basic education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Olsen (2014) explored the needs of youth into adulthood and concluded that learning how to apprehend new forms of learning, developing non-cognitive skills, and connecting learning to pragmatic experiences make the process of learning complex for these learners to make the transition. Davis (2014b) concurs with Olsen's assessment of the complexity of the youth to adult transition and further explains that finding self-agency is critical for these learners to transition educationally. Employing ethnodrama to explicate the experiences of GED students, Davis (2014a) also shows that students' past experiences with school, their social positions within the educational system, life circumstances such as moving or pregnancy impacted their leaving school and influenced their decision to return to school.…”
Section: Lifelong Learning Skillssupporting
confidence: 74%
“…Olsen (2014) explored the needs of youth into adulthood and concluded that learning how to apprehend new forms of learning, developing non-cognitive skills, and connecting learning to pragmatic experiences make the process of learning complex for these learners to make the transition. Davis (2014b) concurs with Olsen's assessment of the complexity of the youth to adult transition and further explains that finding self-agency is critical for these learners to transition educationally. Employing ethnodrama to explicate the experiences of GED students, Davis (2014a) also shows that students' past experiences with school, their social positions within the educational system, life circumstances such as moving or pregnancy impacted their leaving school and influenced their decision to return to school.…”
Section: Lifelong Learning Skillssupporting
confidence: 74%
“…Despite drastic cuts to family literacy programmes in recent years, large numbers of parents/caregivers continue to enrol, making the ABE system arguably one of the most significant contexts for addressing the health literacy needs of this population. The ABE system also serves an increasing number of youth aged 16-24 (Davis, 2014), a population that to date has received little attention in health literacy research . The ABE system also serves historically hard-to-reach populations, such as immigrant and refugee adults without legal documentation, as well as English language learners with little to no print skills in the primary language, and limited formal schooling experience (one of the fastest growing sectors of English language programming; see Center for Applied Linguistics, 2010).…”
Section: Adult Basic Education In the Usmentioning
confidence: 99%
“…Despite drastic cuts to family literacy programmes in recent years, large numbers of parents/caregivers continue to enrol, making the ABE system arguably one of the most significant contexts for addressing the health literacy needs of this population. The ABE system also serves an increasing number of youth aged 16-24 (Davis, 2014), a population that to date has received little attention in health literacy research (Manganello, 2008). The ABE system also serves historically hard-to-reach populations, such as immigrant and refugee adults without legal documentation, as well as English language learners with little to no print skills in the primary language, and limited formal schooling experience (one of the fastest growing sectors of English language programming; see Center for Applied Linguistics, 2010).…”
Section: Adult Basic Education In the Usmentioning
confidence: 99%